Analisis Hukum Dalam Menyelesaikan Konflik Penanaman Modal Asing di Kawasan Ekonomi Khusus Pulau Rempang Kota Batam - Novri Yanti Elisabeth Sirait; Anjelina Sitinjak; Melpa Citra Bestari Sinaga; Muhammad Fajar Hidayat (Lembaga Pengembangan Kinerja Dosen, 2024)
Development is one way to create people's welfare. Therefore, the results of development must be able to be enjoyed by all people as a form of increasing physical and spiritual welfare in a fair and equitable manner. To stimulate economic growth and focus investment policies, the government is aggressively creating Special Economic Zones (KEK) in various regions. It is hoped that people can feel the maximum benefits. Batam City has a strategic location, one of which is Rempang Island which has a lot of potential that can be developed, both in the tourism, economic and social sectors. However, there are misunderstandings between local communities and the government, giving rise to quite serious conflicts due to territorial struggles. So there is a need for efforts to protect the rights of people affected by the clearing of land for investment purposes on Rempang Island, Batam, which can be done with preventive efforts, repressive efforts or prosecution efforts. So this research uses normative juridical research methods, namely focusing on the analysis of doctrine, norms and the application of certain legal principles in dealing with certain legal subjects. With a statutory regulation approach and conceptualization method, it uses technical analysis of legal materials to solve frozen problems.